Modern Technology Urgency in the Development of Islamic Law - Andi Salman Maggalatung (Universitas Islam Negeri Jakarta, 2019)
This paper aims at examining the advancement of modern technology and its intersection with Islamic law. Some areas discussed are related to worship, family law, and medical treatment using organ transplantation. This study finds that some areas of Islamic law are statics, while others are dynamics. The modern technology has provided convenience for human beings such as the use of technology in pilgrimage; the determination of paternity; having baby through IVF, and the medical treatment for patients with heart failure. On the other hand, modern technology cannot change Islamic provisions on worship. Penelitian ini mencoba membahas kemajuan teknologi modern dan dampaknya terhadap hukum Islam, termasuk di bidang ibadah, hukum keluarga, dan perawatan medis seperti penggunakan transplantasi organ. Beberapa bidang hukum Islam bersifat statis sementara yang lain bersifat dinamis. Teknologi modern telah memberikan kemudahan bagi manusia seperti penggunaan teknologi dalam berhaji; penentuan ayah terhadap bayi melalui IVF, dan perawatan medis untuk pasien dengan gagal jantung. Di sisi lain, teknologi modern tidak dapat mengubah ketentuan Islam tentang ibadah.